Açai (Euterpe oleracea) and its contributions to achieve acceptable daily intake of essential fatty acids (Research, Society and Development, 2020)
The objective of this study was to characterize and compare purple açaí pulps (coarse-PAC, medium-PAM, and fine-PAF) and white açaí (coarse-WAC) pulps in terms of their centesimal composition, phenolic compounds (PC) profile and fatty acid profile (FA). Thus, it will be able to evaluate the contribution of essential FA that are present in these pulps to reach an acceptable daily intake of FA. The average composition of the samples was determined by conventional methods, whereas the PC profile was identified by mass spectrometry. On the other hand, the amount of FA was carried out by gas chromatography. The moisture content varied between 82.74-92.00 g/100g. With respect to ash content, all samples differed ranging from 0.42-0.94 g/100g. Regarding lipids, the PAC sample (10.67 g/100g) had the highest content, while the PAF (2.94 g/100g) had the lowest content. The contents of protein and carbohydrates varied respectively from 1.21 to 1.62 g/100g and 2.88 to 5.24 g/100g. As for the PC profile, 21 compounds were identified: 11 in the negative mode and 10 in the positive mode. Among these compounds, caffeic acid and crosserial stand out: they were present in all samples. Concerning the FA profile, there was a predominance of unsaturated, especially monounsaturated, fatty acids as oleic acid (56.80-59.50%). As for the contribution of polyunsaturated FA in reaching the recommendations of essential FA, the PAC sample stands out again, with contributions of at least 17.71% for linoleic FA and 12.06% for alpha-linolenic FA per usual portions of consumption.